ANALYSIS OF PARENTS' SOCIAL ECONOMIC STATUS TOWARDS CARIES STATUS IN CHILDREN - Fahmi; Liana, Intan (Journal Dental Health, 2022)
A concise and factual abstract is required (maximum length 200 words). The abstract should state briefly the purpose of the research, the principal results, and major conclusions. An abstract is often presented separately from the article, so it must be able to stand alone. References should therefore be avoided, but if essential, they must be cited in full, without reference to the reference list. Non-standard or uncommon abbreviations should be avoided, but if essential they must be defined at their first mention in the abstract itself. Abstract in italics, spacing 1, size 11, Font Book Antiqua also includes keywords. The number of words for the abstract is min. 150-200 words, which contain the problem, objectives, methods, and results. Keywords are a minimum of 3 (three) and a maximum of 5 (five) words that reflect the content of the manuscript. Please avoiding general and plural terms and multiple concepts (avoid, for example, 'and', 'of'). Separate each keyword with a ";" on every word. Be frugal with abbreviations: only abbreviations that are familiar in the field are eligible. These keywords will be used for indexing purposes.